PWE-047 Therapeutic drug monitoring for infliximab & adalimumab in IBD: practice patterns, understanding & interpretation. (8th June 2018) - Samaan, Mark; Arkir, Zehra; Irving, Peter; Chuter, Charlotte
Abstract : Introduction: The use of therapeutic drug monitoring (TDM) for infliximab and adalimumab in the treatment of inflammatory bowel disease (IBD) is becoming increasingly commonplace. In cases of non-response (primary or secondary) TDM can provide a clearer understanding of the cause of treatment failure and offer a rationale for steps taken to recapture response. However, several factors regarding its use remain uncertain such as minimum therapeutic thresholds, the relevance of antidrug antibodies found in the presence of detectable drug, and the benefits of TDM during remission. Methods: We designed a survey that included 5 TDM-based clinical scenarios, for which the 'most appropriate' responses were based on the Building Research in IBD Globally (BRIDGe) groups 'Anti-TNF Optimizer' (http://www.bridgeibd.com/anti-tnf-optimizer). This resource combines available TDM evidence with expert consensus. A link to our online survey tool was sent to various IBD clinician groups in June 2017 including members of the British Society of Gastroenterology, Royal College of Nursing IBD Network and the gastroenterology special interest group of the UK Clinical Pharmacy Association. Results: We received 142 responses. Of these, 110 (77%) were complete, comprising 50 (45%) consultants, 30 (27%) trainees, 25 (23%) IBD nurse specialists and 5 (5%) gastroenterology pharmacists, and were used for analysis. Over half (61, 55%) only carry out TDM in non-response. The remainder use TDM routinely, during stable maintenance therapy for patients in remission. Only 15 (14%) respondents reported being clear and confident in their understanding of the difference between drug-sensitive and drug-tolerant assays. Moreover, most (82, 75%) were unsure as to which type their laboratory uses. Lower therapeutic thresholds used by clinicians were variable (figure 1). Consultants, high-frequency TDM users (>3 requests/month) and clinicians with larger anti-TNF cohorts (>100 patients) were significantly more likely to select the 'most appropriate' answer to at least 1 of the 5 TDM scenarios (figure 2). Conclusions: These results demonstrate marked heterogeneity in the practical use, understanding and interpretation of biologic TDM in IBD. Biologic decision-making, informed by TDM, should involve consultation with experienced clinicians who are frequent TDM users, ideally, as part of a multidisciplinary, biologics-focused IBD meeting.